Islamic Journalism Strategy in Media Transformation from Print to Digital - Alfiansyah Husin (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Bandar Lam, 2026)
Islamic journalism is a model of journalistic practice that integrates the principles of media professionalism with the ethical values of Islamic teachings. This research or study discusses the working principles of the Islamic Journalism Code of Ethics, which is based on the Qur'an, Sunnah, and noble morals as guidelines in the production and publication of information. Through a descriptive approach, it was found that the main principles of Islamic journalism include the obligation of verification (tabayyun), honesty and objectivity, moral and social responsibility, and a commitment to upholding human honor and dignity. Islamic journalism rejects all forms of information manipulation such as hoaxes, slander, and propaganda, and positions the media as a means of da'wah and public enlightenment through the values of amar ma'ruf nahi munkar. This study emphasizes that Islamic journalism is not only a news reporting system, but also an ethical practice that aims to build a knowledgeable, just, and moral society. Thus, the Islamic journalism code of ethics is an important foundation for the creation of responsible and beneficial reporting in modern social life.